Formulation and Evaluation of Fixed-Dose Combination of Bilayer Gastroretentive Matrix Tablet Containing Atorvastatin as Fast-Release and Atenolol as Sustained-Release. (2nd January 2014) - Dey, Sanjay; Chattopadhyay, Sankha; Mazumder, Bhaskar
Abstract : The objective of the present study was to develop bilayer tablets of atorvastatin and atenolol that are characterized by initial fast-release of atorvastatin in the stomach and comply with the release requirements of sustained-release of atenolol. An amorphous, solvent evaporation inclusion complex of atorvastatin with β -cyclodextrin, present in 1 : 3 (drug/cyclodextrin) molar ratio, was employed in the fast-release layer to enhance the dissolution of atorvastatin. Xanthan gum and guar gum were integrated in the sustained-release layer. Bilayer tablets composed of sustained-release layer (10% w/w of xanthan gum and guar gum) and fast-release layer [1 : 3 (drug/cyclodextrin)] showed the desired release profile. The atorvastatin contained in the fast-release layer showed an initial fast-release of more than 60% of its drug content within 2 h, followed by sustained release of the atenolol for a period of 12 h. The pharmacokinetic study illustrated that the fast absorption and increased oral bioavailability of atorvastatin as well as therapeutic concentration of atenolol in blood were made available through adoption of formulation strategy of bilayer tablets. It can be concluded that the bilayer tablets of atorvastatin and atenolol can be successfully employed for the treatment of hypertension and hypercholesterolemia together through oral administration of single tablet.